O desenvolvimento espiritual integrado ao planejamento estratégico pessoal - Vasconcelos, Fábio de Souza (2010)
This research aims to develop a model of spiritual development with an emphasis on practicing Spiritual Planning, which optimizes the Personal Strategic Planning. Also use the approach of qualitative research, through the use of technical literature. To achieve the objectives, the study describes the models that have Personal Strategic Planning, with relevance, the spirituality as an integral part, and offers topics like: Spirituality and its conceptual foundations, Spirituality and Management, Spirituality and Existential Bridges between individuals, groups and organizations, Spiritual Capital, Spirituality and Neuroscience, in the contemporary literature. The proposed model consists of six (6) stages of development: Awareness of the Realities (Awareness of World Vision), Work of Meditation (Internalization), Desire for Interior Change, Spiritual Completeness (Change and Clarity of Values), Spiritual Restructuring (Self-Reconstruction in Relationships) and Mission (Existential Purpose).